2020
DOI: 10.1101/2020.09.24.20200436
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

When it is available, will we take it? Public perception of hypothetical COVID-19 vaccine in Nigeria

Abstract: COVID-19 pandemic is a global public health threat facing mankind. There is no specific antiviral treatment for COVID-19, and no vaccine is currently available. This study aims to understand the perception of the public towards hypothetical COVID-19 vaccine in Nigeria. We conducted a cross-sectional survey in August 2020 across the 36 states of Nigeria using an online questionnaire. The questionnaire includes sections on the demographic characteristics of the respondents and their perception regarding hypothet… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 29 publications
1
41
3
Order By: Relevance
“…27 Kasozi et al in Uganda found that 87% of healthcare workers (n=260, September-October 2020) did not think COVID-19 vaccines were necessary to stop the pandemic. 22 While studies in Nigeria found that respondents not wanting a COVID-19 vaccine noted that "the immune systems is sufficient" 26 and "the vaccine is not needed since infection is harmless". 12 People had many questions about why a vaccine is needed given perceptions of innate immunity in Africa and the epidemiological risk profile on the continent.…”
Section: There Were Different Drivers Of Low Perceived Risk Of Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…27 Kasozi et al in Uganda found that 87% of healthcare workers (n=260, September-October 2020) did not think COVID-19 vaccines were necessary to stop the pandemic. 22 While studies in Nigeria found that respondents not wanting a COVID-19 vaccine noted that "the immune systems is sufficient" 26 and "the vaccine is not needed since infection is harmless". 12 People had many questions about why a vaccine is needed given perceptions of innate immunity in Africa and the epidemiological risk profile on the continent.…”
Section: There Were Different Drivers Of Low Perceived Risk Of Covid-19mentioning
confidence: 99%
“…4 Adebisi et al (n= 517, Aug 2020) in Nigeria found that among those who would not accept the vaccine, 37% the stated that the clinical trials had been inadequate. 26 In the PERC survey, a total of 22% of respondents in Ethiopia, Kenya, Uganda, Ghana, Senegal and Zimbabwe believed that the development of the COVID-19 vaccines had been rushed. 6 Participants who would likely not accept the vaccine, from a study in South Africa, voiced concerns: "According to the knowledge I got from school the long term effects of the vaccine are unknown and the vaccine has not been tested…”
Section: Concerns About the Covid-19 Vaccines Often Related To Safety And Side Effectsmentioning
confidence: 99%
“…Furthermore, African governments need to start devising means and strategies to ensure inclusive access to COVID-19 vaccine when it becomes available. 18 …”
Section: Commentarymentioning
confidence: 99%
“…However, intention to take COVID-19 vaccine depends on the confidence and safety of the vaccine. Amid the pandemic, healthcare workers have also shown skepticism towards vaccine even in developed countries [13, 14]. This is a point of great concern for the world since healthcare workers are the most credible and trusted sources of the information and their doubt on vaccine will subjugate other people to follow the same pattern of believe.…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted March 24, 2021. ; https://doi.org/10.1101/2021.03.20.21253892 doi: medRxiv preprint and socioeconomic benefits is the most effective mean to end the pandemic [13]. As of December 2020, several vaccines against COVID-19 have been authorized [14].…”
Section: Introductionmentioning
confidence: 99%